From the Treaty of Rome to Cotonou: Continuity and change in the governance of EU-Africa relations - Raimundo, A. (2022)
This chapter provides a long-term and comprehensive assessment of the institutional frameworks governing EU-Africa relations, from the 1950s Rome Treaty to the 2000s Cotonou Agreement. It takes stock of how the set of institutions, rules, narratives and practices that govern those relations have evolved historically, examining their origins, nature and effects. The chapter considers how key actors dynamically interacted within these institutional frameworks and their main contexts to shape concrete policy outcomes. It explores what have been the principal arrangements governing those delineated relations: the Rome Treaty, the Yaoundé conventions, the Lomé conventions and the Cotonou Agreement. The EU launched a public consultation on the future of the ACP-EU cooperation post 2020 and an evaluation of the first 15 years of Cotonou. The EU’s self-assessment pointed to progress on aspects such as poverty reduction, trade flows, peace and security, while recognising weaknesses in relation to political dialogue, human rights, migration and involvement of non-state actors.